Analisis Penggunaan Aplikasi KAHOOT dalam Pembelajaran IPA - Lisnani Lisnani*; Gunadi Emmanuel (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
KAHOOT application is a web-based application that is used in learning as an application to test the ability of a group of people. This type of research is a type of qualitative and quantitative research. The purpose of this study is twofold: First, to get an overview of the process and results of student quizzes in High Class Science Learning courses through the use of the KAHOOT application for students of the Second Semester PGSD Study Program Musi Charitas Catholic University. Second, knowing the responses of PGSD Study Program Students in Second Semester Musi Charitas Catholic University who took part in the learning process using the KAHOOT application in the High Class Science Learning course. The sample in this study was the second semester students of the PGSD study program Palembang Musi Charitas Catholic University totaling 26 people. Data collection techniques using tests and questionnaires. Data were analyzed descriptively qualitative-quantitative. There are 2 results obtained in this study, namely: First, the learning process becomes more exciting, interesting, and challenging because it is accompanied by music and time to work on the questions so that students are trained in speed and accuracy in answering questions. The average value of student quizzes using the KAHOOT application is 66.69. Second, students gave a positive response to the use of the KAHOOT application as seen from the results of the questionnaire in which some students expected the completion of the quiz to be carried out using the KAHOOT application in the future